E-LEARNING BERBASIS SOCIO-SCIENTIFIC ISSUES DAN NILAI-NILAI HINDU: SOLUSI PEMBELAJARAN DARING SISWA POST-MILLENIAL AGAMA HINDU DI ERA PANDEMI COVID-19 - Vina Melinda (Veda Jyotih: Jurnal Agama dan Sains, 2022)
Online learning in the era of the covid-19 pandemic requires Hindu religious teachers and students to get used to the learning process using technology. This study aims to analyze the profile of e-learning used by Hindu religious teachers in the era of the covid-19 pandemic, as well as recommendations for learning media that can be integrated into schools in learning Hinduism. Several e-learning applications have been used well in various schools, but there is no content that characterizes them. The learning content provided by the teacher to students has not integrated scientific knowledge, students are not faced directly with problems that occur in the surrounding environment, even character education and Hindu values ​​are less associated with social problems around students. Researchers recommend developing e-learning based on Socio-Scientific Issues and Hindu values ​​as an alternative solution for the post-millennial generation in online learning. The results of this study can be used as empirical evidence that e-learning needs to be developed, especially the learning content section.